Socio-Demographic Characteristics and Concerns about Water Quality Issues of Master Gardener Program Volunteers - Tatiana Borisova; Michael Smolen; Maria Pilar Useche; Jon Calabria; Nickola Sochacka; Damian Adams; Diane Boellstorff; Jason Evans; Robert Mahler (EDIS, 2014)
To respond to residents’ informational needs, the Cooperative Extension Service offers a variety of volunteer training and certification programs. Who participates in such programs? What types of audiences are being reached? Do such programs increase knowledge and change behavior of the volunteers? In this article, we attempt to answer these questions by summarizing existing studies and using responses to a regional public survey, and by focusing on the Master Gardener program and surface water quality issues as examples. This 7-page fact sheet was written by Tatiana Borisova, Michael Smolen, Maria Pilar Useche, Jon Calabria, Nickola Sochacka, Damian Adams, Diane Boellstorff, Jason Evans, and Robert Mahler, and published by the UF Department of Food and Resource Economics, May 2014.